Taxonomic revision of the Cis-Andean species of Mylossoma Eigenmann & Kennedy, 1903 (Teleostei: Characiformes: Serrasalmidae) - Mateussi, Nadayca T. B. [UNESP]; Oliveira, Claudio [UNESP]; Pavanelli, Carla S. (Magnolia Press, 2018)
A revision of the cis-Andean species of Mylossoma is presented. Four species were recognized: M. albiscopum and M. aureum from the rio Amazonas and rio Orinoco basins; M. duriventre, from the rio Paraguai, lower rio Parana and rio Uruguai basins; and M. unimaculatum, an endemic species from the Tocantins-Araguaia system. Both Mylossoma albiscopum and M. unimaculatum were removed from the synonymy of Mylossoma duriventre, which had its occurrence range restricted to the La Plata basin. The recognition of these four valid species corroborates the results of a previous DNA barcode study. Redescriptions of each species, and an identification key for the genus are provided.
Keywords: biodiversity; freshwater fishes; systematics; taxonomy